If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + x) + -2 = 1 (5 * 3 + x * 3) + -2 = 1 (15 + 3x) + -2 = 1 Reorder the terms: 15 + -2 + 3x = 1 Combine like terms: 15 + -2 = 13 13 + 3x = 1 Solving 13 + 3x = 1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 3x = 1 + -13 Combine like terms: 13 + -13 = 0 0 + 3x = 1 + -13 3x = 1 + -13 Combine like terms: 1 + -13 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| 12x-9x= | | -6(-2x+3-4x)+20=5(2-14x-5) | | ln(x^2-4x+5)=0 | | 4a*3b= | | 138-7x=20x+15 | | 7-10x=124-31x | | 4n=44 | | -3(8+7t)=2t+2(4t-53-t) | | -3t(8+7t)=2t+2(4t-53-t) | | 53-2x=7x+21 | | 153-6x=5x+21 | | 2y-1=10y-65 | | -42.4x=-84.8 | | 7.7x=-84.7 | | 9.5x=-95 | | 9.5=-95 | | 18-y-6y= | | 8(x+2)=2(x+26) | | 3(x-3)=45-3x | | 6x-5=131-11x | | x(5-x)=25 | | 10y-4=16 | | 11-4(3-2x)=5(2x+1)+1 | | 11x+1=3x+57 | | X(x-5)=25 | | -5*(-1)= | | 3v=108 | | 3v=105 | | 11-4(3-2x)=9(2x+1)+1 | | 4a-4=16 | | 64-(6-5*5)= | | 18p-3=6 |